2024
DOI: 10.1186/s40364-024-00561-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring non-invasive precision treatment in non-small cell lung cancer patients through deep learning radiomics across imaging features and molecular phenotypes

Xingping Zhang,
Guijuan Zhang,
Xingting Qiu
et al.

Abstract: Background Accurate prediction of tumor molecular alterations is vital for optimizing cancer treatment. Traditional tissue-based approaches encounter limitations due to invasiveness, heterogeneity, and molecular dynamic changes. We aim to develop and validate a deep learning radiomics framework to obtain imaging features that reflect various molecular changes, aiding first-line treatment decisions for cancer patients. Methods We conducted a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…For patients who are difficult to undergo surgery or biopsy, or whose pathology cannot be decided after biopsy, distinguishing between lung squamous cell carcinoma and adenocarcinoma is a widespread problem that troubles clinical There have been many literature reports on the application of imaging features for pathological prediction in the past. [5][6][7][8][9][10][11][12][13]17,[23][24][25][26][27][28][29][30][31][32][33] Han et al found that a model for distinguishing lung squamous cell carcinoma and lung adenocarcinoma was constructed using CT texture features, with an AUC of 0.803, 5 Zhang et al established a model based on the variation of iodine concentration in enhanced CT, with an AUC of 0.871, 7 Fukuma et al established a model based on the attenuation rate of enhanced CT, with an AUC of only 0.625, 8 Jiang et al established a model based on the perfusion parameters of brain metastases, with an AUC of 0.845, 9 Tomori et al established a model using a combination of PET-CT…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are difficult to undergo surgery or biopsy, or whose pathology cannot be decided after biopsy, distinguishing between lung squamous cell carcinoma and adenocarcinoma is a widespread problem that troubles clinical There have been many literature reports on the application of imaging features for pathological prediction in the past. [5][6][7][8][9][10][11][12][13]17,[23][24][25][26][27][28][29][30][31][32][33] Han et al found that a model for distinguishing lung squamous cell carcinoma and lung adenocarcinoma was constructed using CT texture features, with an AUC of 0.803, 5 Zhang et al established a model based on the variation of iodine concentration in enhanced CT, with an AUC of 0.871, 7 Fukuma et al established a model based on the attenuation rate of enhanced CT, with an AUC of only 0.625, 8 Jiang et al established a model based on the perfusion parameters of brain metastases, with an AUC of 0.845, 9 Tomori et al established a model using a combination of PET-CT…”
Section: Discussionmentioning
confidence: 99%